KEPERCAYAAN DIRI SISWA SAAT MENGIKUTI KEGIATAN EKSTRAKURIKULER SENI TARI DI SDN MOJOWARNO 1 KABUPATEN JOMBANG - Siti Rokhimatun Ni’mah; Desty Dwi Rochmania (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
. The research uses qualitative research with qualitative descriptive approach. The object of this research in SDN Mojowarno 1 jombang district. Data collection thrugh observation techniques, interviews, and documentation techniques. Data analysis techniques are carried out thrugh data reduction stages, display or presentation of data and drawing conclusions. To test the validity of the data using the credibility test, extending the observation and increasing the accuracy of the research.The extracurricular dance activities at SDN Mojowarno 1 primary school are most superior extracurricular activities. And there is also an activity called P5 title. Students who take part in extracurricular dance are presented in the P5 title activity, where they are presented they usually wear dance costumes or simple costumes. After the performance, the students become very optimistic. Extracurriculars of dance at SDN Mojowarno 1 primary school often participates in competitions at the district level. Even as a repsentative and directly appointed by sub-district. Have also won 1 st place from the sub district and 3 rd place from the district.The result showed that the characters of students who take part in dance extracurricular activities have different characters. At the beginning of participating in extracurricular dance activities, there are students who are not confident to display their abilities in public. However, after participating in training every day, students’ self-confidence appears in an confident attitude, has high enthusiasm, has independence and an attitude of responsibility.